Temporal change in channel form and hydraulic behaviour of a tropical river due to natural forcing and anthropogenic interventions - Sarkara, Biplab (2024)
Assessing the degradation of river channels is crucial in the Anthropocene era, particularly in the deltaic areas worldwide. The present study aims to investigate the degradation of the Mathabhanga-Churni River giving emphasis on the temporal change of channel morphology and hydraulic behaviour and comparing the current situation with the historical past based on planform morphology and meander geometry of 118 meander loops, and width, depth, cross-sectional area, and hydraulic behaviour (velocity, discharge, stream power) at 47 cross-sections. The absence of lateral dynamicity, the static character of channel sinuosity during the last century (1913–2018), and the constant meander morphology reflects the static meander geometry and degradation of the river. The reduction of average channel width, depth, and cross-sectional area supports the falling trend of channel forms. Findings on hydraulic behaviour indicate declining discharge (~50% reduction during 1915–2018) that induces the present-day downscaled velocity and lowered stream power. Neotectonics (eastward tilting of the Bengal delta) and anthropogenic stressors such as stream crossings, agriculture on river beds, brickfields, and urbanisation have a severe impact on the hydromorphology of the channel, turning the active river into a stagnant and polluted channel.